An RNA vaccine against adrenomedullin reduces angiogenesis and tumor burden in a syngeneic metastatic melanoma mouse model - Tadic, Srdan; Ochoa-Callejero, Laura; Narro-Íñiguez, Judit; García-Sanmartín, Josune; Martínez, Alfredo (Frontiers in Immunology, 2025)
IntroductionAdrenomedullin (AM) is an autocrine/paracrine growth factor as well as a crucial regulator of angiogenesis and immune response. AM is overexpressed by most solid tumors, which makes it a good target for anti-tumor therapy.MethodsIn this study, we designed and tested an mRNA vaccine directed against a fusion antigen composed by a small piece of keyhole limpet hemocyanin (KLH), as a hapten, and mouse AM. The in vitro-synthesized mRNA was encapsulated in lipid nanoparticles (LNPs) and injected in C57BL/6 mice. Empty LNPs were used as a negative control. After five immunizations, B16-F10 melanoma cells were injected through the tail vein to induce lung metastases. In addition, transgenic mice expressing green fluorescent protein in the blood vessels (SMAA-GFP) were also immunized with both LNP types to assess the potential side-effects of the vaccine on normal blood vessels.ResultsAntibody titers against AM and the number of CD8+ T cells were significantly higher in AM-immunized mice than in negative controls. Furthermore, the number and size of the lung metastases, as well as the number of blood vessels, were significantly reduced in the AM-immunized group. In addition, no significant differences were observed in the number and distribution of existing blood vessels after immunization of the SMAA-GFP animals.DiscussionIn summary, we have shown that an mRNA vaccine against the fusion KLH-AM peptide was able to break peripheral immunotolerance and induce a specific response against the angiogenic factor AM thus reducing tumor burden in the absence of disturbances to normal blood vessels.